Examination of a new mobile intermittent pneumatic compression device in healthy adults. (2nd June 2020) - Chohan, Ambreen; Abram, Simon; Parkes, Amy; Haworth, Lauren; Whitaker, Justine C.
Abstract : Objective: Intermittent pneumatic compression (IPC) is an alternative method of compression treatment designed to compress the leg and mimic ambulatory pump action to actively promote venous return. This study explores the efficacy of a new portable IPC device on tissue oxygenation (StO2 ) in two sitting positions. Method: In this quantitative, healthy single cohort study, participants were screened and recruited using Physical Activity Readiness Questionnaire (PAR-Q, Canada). Participants attended two separate one-hour sessions to evaluate StO2 in an upright chair-sitting position and in a long-sitting position. StO2 was recorded for 20 minutes before, during and after a 20-minute intervention of the IPC device (Venapro, DJO Global, US). Results: A total of 29 healthy volunteers took part in the study. A significant difference was seen between the two seating positions (p=0.003) with long-sitting showing a 12% higher StO2 level than chair-sitting post-intervention. A similar effect was seen in both sitting positions when analysing data over three timepoints (p=0.000). Post-hoc pairwise comparisons showed that significant improvements in StO2 (p≤0.000) were seen from baseline, throughout the intervention, continuing up to 15 minutes post-intervention, indicating a continued effect of the device after a short intervention. Conclusion: Increasing StO2 through short intervention sessions with this portable device has potential for use within various health and sports-based practices, improving tissue health, potentially reducing postoperative deep vein thrombosis (DVT) risk or inflammation. Such devices lend themselves to wide self-management implementation.